The Current State of Food Security in Kazakhstan, in the Context of Eurasian Economic Union. Environmentally Overview in the Case of Climate Change's Scenarios - ZHENSKHAN, Darima; PYAGAY, Alexandr; BESPAYEVA, Roza; KADRINOV, Maulet; OMARKHANOVA, Zhibek; TATIKOVA, Assiya (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).08, 2022)
In the context of changing climatic factors, for the purpose of food security, it is necessary to use certain quantitative components of the global food system. This research article presents a comprehensive analysis of the current state of food security in the Republic of Kazakhstan in connection with the Eurasian Economic Union, including the agricultural system of the countries of Eurasia and food trade, an analysis of the main indicators of agriculture and their spatial and temporal characteristics from 1991 to 2021. The profound impact of COVID-2019 on food systems has been described. We scientifically substantiate the importance of maintaining a balance of interests of the common market for agricultural products and protecting the sovereignty of the states that are members of the EAEU, in the context of assuring measures to ensure food security and climate changes. Taking into consideration the main economic indicators of the agro-industrial complex, we will conduct a comprehensive analysis of the volume of agricultural production determine the level of per capita consumption of basic food products. Despite the achievements of Kazakhstan in the agricultural sector in spatial and temporal changes, we identify specific problems that negatively affect the growth of its production potential. As a result, we will reveal the causes of price instability, the lack of access to socially significant goods in Kazakhstan, and also offer some ways to solve these in the conditions of climate changes.